Cytomegalovirus Infection in Ireland: Seroprevalence, HLA Class I Alleles, and Implications. Issue 6 (February 2016) - Hassan, Jaythoon; O'Neill, Derek; Honari, Bahman; De Gascun, Cillian; Connell, Jeff; Keogan, Mary; Hickey, David
Abstract : Abstract: Cytomegalovirus (CMV) infections occur worldwide and primary infection usually occurs in early childhood and is often asymptomatic whereas primary infection in adults may result in symptomatic illness. CMV establishes a chronic latent infection with intermittent periods of reactivation. Primary infection or reactivation associate with increased mortality and morbidity in those who are immunocompromised. Transplacental transmission may result in significant birth defects or long-term sensorineural hearing loss. We performed a study to determine the CMV seroprevalence and the association between HLA Class I alleles and frequency of CMV infection in Ireland. The presence of CMV IgG, a marker of previous CMV infection, was determined for a cohort of 1849 HLA typed solid organ transplant donors between 1990 and 2013. The presence of CMV IgG was correlated with HLA type. The CMV seroprevalence in solid organ transplant donors was 33.4% (range 22–48% per annum) over the time period 1990 to 2013. Multivariate logistic regression analysis showed that both age and HLA alleles were associated with CMV seropositivity. A significant and positive relationship between age and CMV seropositivity was observed (OR = 1.013, P  < 0.001, CI [1.007, 1.019]). Chi-square analysis revealed that the female gender was independently associated with CMV seropositivity ( P  < 0.01). Seroprevalence in women of reproductive age (20–39 years) was significantly higher than men of the same age (37% vs 26%, P  < 0.01). The frequencies of HLA-A1, HLA-A2, and HLA-A3 in our cohort were 40.8%, 48.8%, and 25.9%, respectively. Logistic regression analysis showed that the presence of HLA-A1 but not HLA-A2 or HLA-A3 was independently associated with CMV seronegativity ( P  < 0.01). Interestingly, individuals who co-expressed HLA-A2 and HLA-A3 alleles were significantly more likely to be CMV seropositive ( P  < 0.02). The frequencies of HLA-B5, HLA-B7, and HLA-B8 in our cohort were 6.1%, 31.2%, and 30.8%, respectively. The presence of the most common inherited haplotype in the Irish population, HLA-A1, B8 was significantly associated with CMV seronegativity (OR = 1.278, P  < 0.001, CI [1.049, 1.556]). CMV seroprevalence is lower in Ireland compared with other countries. The high frequency of HLA-A1 in the Irish population may, in part, have a role in the reduced susceptibility to CMV infection.